2018
DOI: 10.1007/s00018-018-2819-7
|View full text |Cite
|
Sign up to set email alerts
|

Ciliary proteins Fap43 and Fap44 interact with each other and are essential for proper cilia and flagella beating

Abstract: Cilia beating is powered by the inner and outer dynein arms (IDAs and ODAs). These multi-subunit macrocomplexes are arranged in two rows on each outer doublet along the entire cilium length, except its distal end. To generate cilia beating, the activity of ODAs and IDAs must be strictly regulated locally by interactions with the dynein arm-associated structures within each ciliary unit and coordinated globally in time and space between doublets and along the axoneme. Here, we provide evidence of a novel ciliar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
66
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(73 citation statements)
references
References 70 publications
7
66
0
Order By: Relevance
“…We found that FAP57 co-elutes with the I1 tether head subunits during FPLC fractionation (Figure 4, Supplemental Table 4). Although none of these proteins require FAP57 for assembly into the axoneme (Table 2) nor vice versa (Supplemental Figure 3; see also Urbanska et al, 2018), collectively the data suggest that FAP57 is located in close proximity to both I1 dynein and the MIA complex.…”
Section: Fap57 Forms An Extended Structure Within the 96 Nm Repeat Thmentioning
confidence: 76%
See 1 more Smart Citation
“…We found that FAP57 co-elutes with the I1 tether head subunits during FPLC fractionation (Figure 4, Supplemental Table 4). Although none of these proteins require FAP57 for assembly into the axoneme (Table 2) nor vice versa (Supplemental Figure 3; see also Urbanska et al, 2018), collectively the data suggest that FAP57 is located in close proximity to both I1 dynein and the MIA complex.…”
Section: Fap57 Forms An Extended Structure Within the 96 Nm Repeat Thmentioning
confidence: 76%
“…Five other polypeptides co-eluted with FAP57; these included FAP44, FAP43, FAP244, FAP159, and FAP75, in order of peptide abundance ( Supplemental Table 4). Little is known about FAP159 and FAP75, but FAP43, FAP44, and FAP244 have been identified as subunits of a tether-tether head (T/TH) complex linking the I1 dynein motor domains to the DMT and also interacting with the base of dynein d Kubo et al, 2018;Urbanska et al, 2018). FAP43, FAP44, and FAP244 share structural similarity with FAP57 with respect to the arrangement of their WD repeat and coiled coil domains Kubo et al, 2018), and FAP43 and FAP44 have been proposed to interact with FAP57 in Tetrahymena cilia based on proximity labeling .…”
Section: Identification Of Polypeptides Associated With Fap57 By Massmentioning
confidence: 99%
“…As was shown in studies using model organisms, some mutations can cause small changes in cilia beating [36]. Thus, it is possible that individuals harboring similar mutations have no symptoms or manifest only mild symptoms and are never diagnosed for PCD.…”
Section: Primary Ciliary Dyskinesia (Pcd)mentioning
confidence: 94%
“…To overexpress Kat2-2V5 in the GRL3/GRL4 region, we amplified a 0.8 kb fragment of the GRL4 gene, adding SacII and BglII restriction sites at 5 and 3 ends, respectively (primers in Table S1), and cloned it into a p4T2 vector carrying a neo2 cassette digested with SacII and BamHI. In parallel, the HA coding region and BTU1 3 UTR (untranslated region) were removed from the Kat2-HA-overexpressing plasmid using BamHI and XhoI sites, and were replaced by the 2V5 coding region, followed by 0.6 kb of 3 UTR of BTU1 (transcription terminator) obtained from the native locus expression plasmid [26] using BamHI and EcoRV restriction enzymes and 1.1 kb of the GRL3 gene amplified from the genomic DNA with the addition of EcoRV and XhoI sites at 5 and 3 ends, respectively (Table S1). Next, the GRL4-neo2 fragment was cloned into the pKat2-2V5-GRL3 vector using SacI and Cla I restriction sites.…”
Section: Protein Tagging and Domain Analysismentioning
confidence: 99%